STRATEGI PERENCANAAN SUMBER DAYA MANUSIA UNTUK PENINGKATAN DAYA SAING CV. AJIB BIO SYIFA - Octa Nilam Lukkita (Institut Bisnis Muhammadiyah Bekasi, 2022)
This research was conducted with the intention or purpose of describing human resource management and the problems that occur in the midst of a high level of rivalry, as well as making alternative strategies for CV. Ajib Bio Syifa is a bottled beverage water company located on the island of Lombok. HR is very important to be developed because HR is one of the distinguishing factors between each company. In this research, the research method used descriptive qualitative. While collecting data by making observations and interviews. In order to test the validity of the data, the authors used a triangulation technique. Based on the research results, it can be seen that the company's HR management has been implemented. Because the company has effectively compiled the planning of human resource needs, organizing, and actuating workers. So as to achieve high employee motivation.